METHODS OF INTERPRETATION: EPISTEMOLOGICAL VIEWS OF BAYANI, BURHANI, AND IRFANI - Irfani, Muhammad; Habibi, Muhammad Ikhwan; Rifqiyansyah, Muhammad (Prodi Pendidikan Agama Islam STAI Darul Falah, 2025)
Bayani, Burhani and Irfani epistemology is a part of philosophy that is integrated with sources of interpretive methods. So it is necessary to explore and examine the relevance of Islamic epistemology in analyzing exegetical methods. This research is qualitative descriptive research using a library research approach based on literary sources, journal articles and books related to research. The purpose of this study is to classify the dimensions of tafsir studies that have been devoted by mufasir in contributing to Islamic thought through the holy book of the Qur'an. Bayani, Irfani and Burhani epistemology is a characteristic of Arabic research that originates directly from the teachings of the Prophet Muhammad, his companions and tabi'in. The integration of the Bayani epistemology with the interpretation method is in the historical aspect of bī al-ma'sūr, namely examining the meaning of the message through the text. Meanwhile, Burhani epistemology in its integration with the method of interpretation from the perspective of bī ar-ra'yi, namely revealing messages conveyed through human reason and rational reasoning. Meanwhile, Irfani epistemology reveals the method of interpretation through the al-Isyārī method, namely understanding the message through the intuition of each person's ability after carrying out the stages that go through to obtain intuition (the science of kasyf).